Lactobacillus crustorum ZHG 2-1 as novel quorum-quenching bacteria reducing virulence factors and biofilms formation of Pseudomonas aeruginosa. (January 2020) - Cui, Tianqi; Bai, Fengling; Sun, Mengtong; Lv, Xinran; Li, Xuepeng; Zhang, Defu; Du, Hong
Abstract: Quorum quenching (QQ) activity of crude extract (CE) from Lactobacillus crustorum ZHG 2-1 against Pseudomonas aeruginosa was evaluated at three sub-minimum inhibitory concentrations (MIC) 1.0, 2.0 and 3.0 mg/mL. Agar diffusion method results showed that CE can degrade N -homoserine lactone (AHLs) by 37.1–87.6% at three sub-MICs. Moreover, the degradation activity was further confirmed by gas chromatography-mass spectrometer (GC-MS). The inhibition rate of biofilms and the removal of preformed biofilms of the CE alone and in combination with azithromycin were determined by 96-well plate method. The results demonstrated that CE can significantly enhance the sensitivity of azithromycin to biofilms, and the inhibition rate were 58.4–90.3% at three sub-MICs. Scanning electron microscopy (SEM) images demonstrated that the CE combined with azithromycin can inhibit biofilms formation and reduce the thickness of preformed biofilms. Quantitative real-time polymerase chain reaction analysis indicated that the expressions of quorum sensing (QS)-regulated genes lasI/R and rhlI/R were down-regulated. Additionally, the production of virulence factors, including protease, chitinase, pyocyanin, rhamnolipid, alinate and exopolysaccharide, were also suppressed by CE at three sub-MICs. And all the above effects showed a dose dependent. These results demonstrated that ZHG 2-1 can consider as a novel potential QQ bacteria to against foodborne pathogenic bacteria. Graphical abstract: Lactobacillus crustorum ZHG 2-1 is able to block QS systems of P. aeruginosa. Image 1 Highlights: Lb. crustorum ZHG 2-1 can degrade C4 -HSL and 3-oxo-C12 -HSL. ZHG 2-1 can as QQ bacteria to block QS systems of P. aeruginosa . ZHG 2-1 can serve as antibiofilm agent against P. aeruginosa. ZHG 2-1 can serve as antibiotic-accelerant.